Determinants of Fish Consumption in East Kalimantan, Indonesia: Health Knowledge, Socio-Economic Factors, and Sustainable Fishing and Culturing Practices - Oktawati, Nurul Ovia; Boa, Handayani (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: Fish consumption preferences vary among communities. The issue of fish consumption achievement of East Kalimantan residents which has decreased compared to 2019 has encouraged the government to intensify programs, especially considering socio-economic factors for liking to consume fish. In this study, the issue of fish consumption is also associated with the residents’ knowledge of the benefits of fish nutritional content for health. Aims: This recent study aims to investigate the appreciation of East Kalimantan residents for the health of fish consumption benefits and to analyze factors which influence the fish consumption of East Kalimantan residents. Methods: Data collection was done through a questionnaire completed by 160 people in 10 regency and city sites in East Kalimantan with purposive random sampling method during January to March 2024. Also employing Multiple Linear Regression (MLR) is in data analysis. Results: Most of East Kalimantan residents (85%) appreciate the benefits of fish consumption for their health, even though there are still residents (15%) who lack information and knowledge about its benefits. The residents’ understanding and knowledge cover fish as a rich source of omega-3 fatty acids, high-quality protein, and related with reducing risk of heart disease, stroke, and certain types of cancer. The most residents (90%) approve that the fish protein content is of high quality of protein and vitamins-mineral. In the analysis, all variables that build this model have amounting to 82% (R2) affected into fish consumption residents. Partially, age, income, fish price, ethnic, education, and fish substitute variables significantly influence the fish consumption of East Kalimantan residents at p<0.05. Except, the status at the family variable, it has not influence partially to fish consumption of residents. Conclusion: Residents who understand and know of fish consumption benefit for health are high. The research findings indicate that various variables (age (X1), income (X2), fish price (X3), ethnic (D2), education (D3), and fish substitute (D4) variables) significantly influence the fish consumption of East Kalimantan residents. Hence, to stimulate awareness of fish consumption, the government has to support the residents through more measurable programs for the increase of fish consumption such as socializing the benefit of fish consumption for health and fish eating program. Received: 12 July 2024, Reviewed: 22 July 2024, Revised: 23 August 2024, Accepted: 26 August 2024.